Product and furniture design - Thompson, Rob; Kim, Young Yun (London : Thames & Hudson, 2011)
With some 430 specially commissioned photographs and technical illustrations, this book describes more than 30 manufacturing processes, from the traditional and established to cutting-edge technologies
1. Forming technology -- 2. Joining technology -- 3. Finishing technology
Includes bibliographical references (p. 189-190) and index
Keywords: Furniture design; Industrial design; Manufacturing processes -- Case studies; Product design